Nutritional Knowledge and Body Mass Index among Students at Novena University, Ogume, Nigeria - Andrew, Udi Onoriode; Godswill, Okoro Ogheneyebrorue; Mamerhi, Enaowho Taniyowho; Boma, Douglas (Folia Medica Indonesiana, 2023)
Highlights: • Interviews were conducted on the correlation between nutritional knowledge and BMI among students at Novena University, Ogume, Nigeria. • Most of the students had adequate nutritional knowledge and a low obesity prevalence rate. Abstract: Body mass index (BMI), which is calculated using height and weight, is a rough indicator of body fat. This study aimed to investigate whether there is a significant correlation between nutritional knowledge and BMI among students at Novena University, Ogume, Nigeria. This study was done using a cross-sectional survey. Interviews were conducted with 50 participants from the sample, whose nutritional knowledge and weight status were assessed. The results showed that the students' BMI ranged from 15 to 39, with a mean and standard deviation of 23.93±5.46 cm. There was a positive correlation between the students' nutritional knowledge and their BMI. In conclusion, the majority of Novena University students are knowledgeable about obesity, which likely accounts for their low obesity prevalence rate.